2014
DOI: 10.1111/jfpp.12264
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Aromatic Amine Contents of Kavurma Commercially Cooked in Steam and Copper Cauldron

Abstract: Kavurma is a traditional coarsely diced and cooked meat product in Turkey. Heterocyclic aromatic amines (HCAs), carcinogenic and/or mutagenic compounds in commercial kavurma samples cooked in steam and copper cauldron were determined. Varying levels of 2-amino-3-methylimidazo [4,5-f]quinoline (IQ) (up to 0.07 ng/g), 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx) (up to 15.60 ng/g), 2-amino-3,4-dimethylimidazo[4,5-f]quinoline (MeIQ) (up to 0.10 ng/g), 2-amino-3,7,8-trimethylimidazo[4,5-f]quinoxaline (7,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…LOQ values were: IQx ¼ 0.013 ng g À1 , IQ ¼ 0.029 ng g À1 , MeIQx ¼ 0.081 ng g À1 , MeIQ ¼ 0.047 ng g À1 , 7,8-DiMeIQx ¼ 0.018 ng g À1 , 4,8-DiMeIQx ¼ 0.025 ng g À1 , PhIP ¼ 0.085 ng g À1 , AaC ¼ 0.039 ng g À1 , and MeAaC ¼ 0.035 ng g À1 . These values are comparable with those in the related literature (Messner & Murkovic, 2004;Oz, 2011;Oz et al, 2015;Oz & Kaya, 2011c;Pais et al, 1999;Skog et al, 1998).…”
Section: Ph Valuesupporting
confidence: 93%
See 2 more Smart Citations
“…LOQ values were: IQx ¼ 0.013 ng g À1 , IQ ¼ 0.029 ng g À1 , MeIQx ¼ 0.081 ng g À1 , MeIQ ¼ 0.047 ng g À1 , 7,8-DiMeIQx ¼ 0.018 ng g À1 , 4,8-DiMeIQx ¼ 0.025 ng g À1 , PhIP ¼ 0.085 ng g À1 , AaC ¼ 0.039 ng g À1 , and MeAaC ¼ 0.035 ng g À1 . These values are comparable with those in the related literature (Messner & Murkovic, 2004;Oz, 2011;Oz et al, 2015;Oz & Kaya, 2011c;Pais et al, 1999;Skog et al, 1998).…”
Section: Ph Valuesupporting
confidence: 93%
“…The gradient programme was as follows: 0% B, 0e10 min; 0e23% B, 11e20 min; 23% B, 21e30 min; 0% B, 31e45 min. The injection volume was 10 ml (Oz et al, 2015). The identification of HCAs was carried out by comparing the retention time, UV spectra recorded for standards and HCAs standards spiked samples.…”
Section: Extraction Of Heterocyclic Aromatic Aminesmentioning
confidence: 99%
See 1 more Smart Citation
“…International Agency for Research on Cancer (IARC) demonstrated that HCAs in class 2B such as 2-amino-3,4-dimethylimidazo[4,5-f]quinoline (MeIQ), 2-amino-3, 8-dimethylimidazo[4,5-f]quinoxaline (MeIQx), 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP), 2-amino-9H-pyrido[2,3-b]indole (AaC), 2-amino-3-methyl-9H-pyrido[2,3-b]indole (MeAaC), 3-amino-1,4-dimethyl-5H-pyrido [4,3-b]indole (TrpePe1), 3-amino-1-methyl-5H-pyrido[4,3-b]indole (TrpePe2) and 2-amino-6-methyldipyrido[1,2-a:3 0 ,2 0 -d]imidazole (GluePe1) are possible human carcinogens and 2-amino-3-methylimidazo[4,5-f]quinoline (IQ), in class 2A, is a probable human carcinogen (Skog, 2004). To date, more than 25 different mutagenic and/or carcinogenic HCAs have been isolated and identified (Oz, Cakmak, Zikirov, Kızıl, & Turhan, 2015). The formation and amounts of the HCAs are dependent on many factors such as meat type, cooking duration, cooking temperatures, cooking equipment and methods, pH, water activity, carbohydrates, free amino acids, and creatine (Oz & Kaya, 2011a;Pais, Salmon, Knize, & Felton, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, International Agency for Research on Cancer (IARC) has classified MeIQ, MeIQx, PhIP, AαC, MeAαC, Trp‐P‐1, Trp‐P‐2, and Glu‐P‐1 in class 2B as “possible human carcinogens” and IQ in class 2A as “probable human carcinogens” (IARC, ). HCA species and levels in heat‐treated meat and meat products depend on the presence and concentrations of various factors such as meat type, cooking temperature, cooking time, cooking equipment and method, pH, water activity, level of carbohydrates, free amino acids, creatine, fats, lipid oxidation, and antioxidants and heat and mass transfer levels (Oz, ; Oz, Cakmak, Zikirov, Kizil, & Turhan, ; Oz, Kizil, Zaman, & Turhan, b; Oz, Kizil, & Çelik, ; Oz & Kaya, ; Pais, Salmon, Knize, & Felton, ). HCAs are classified into two main chemical classes as aminoimidazoazoarenes and aminocarbolines (Skog & Solyakov, ).…”
Section: Introductionmentioning
confidence: 99%